The Influence of the Traditional Reporting Model on Fijian Budgetary Addresses - Brown, Alistair (Graduate School of International Development, 2015)
This study analyses the Bainimarama Regime's use of the Indigenous Traditional Reporting model in the government's budget address from 2010 to 2013. It considers how alternative reporting models were interpreted by the Fijian government as a means of displaying various forms of accountability The results of the etic analysis of indigenous budget speech documentation suggest that while a hybridization of reporting models is ostensibly used by the Bainimarama Regime's budgetary speeches to win over the regime's stakeholders, it is the indigenous Traditional Reporting model which informs the regime's budgetary speeches. The implications of the study is that while Western and hybridization reporting models appear to be an acceptable form of modern rationality for developing countries of the Melanesian region, it is really the indigenous Traditional Reporting model that has served the higher purpose of the prevailing Fijian military regime. Ironically, while the exposure of Western Reporting models opens up reporting to indigenous leaders as a form of economic visibility, civic responsibility and open disclosure, the exposure by indigenous leaders to the Western framing process has allowed them to construe the potential closures of these introduced models and thus render an accountability of indeterminate space.